A meta-analysis of factors affecting the adoption of drought-tolerant maize varieties (DTMV) in sub-Saharan Africa - Adechian, Soulé Akinhola; Gouroubera, W. Mori; Baco, Mohamed Nasser; Ogoudou, Christine; Yacoubou, Abdoul-Madjidou; Abdoulaye, Tahirou (Elsevier, 2025)
Drought-tolerant maize varieties (DTMV) have been developed as a climate-resilient agricultural technology to help mitigate food insecurity in sub-Saharan Africa, where climate change significantly impacts crop yields and threatens agricultural sustainability. The adoption of these technologies remains limited, and a range of sometimes contradictory hypotheses are reported. We conducted a meta-analysis to determine the overall adoption rate of DTMV and its key drivers and barriers based on 23 articles identified in Scopus, Web of Science, and Google Scholar across nine countries. Meta-analyses revealed a low overall adoption rate of 11.2 % across subSaharan Africa. Furthermore, moderation analyses revealed a similar pattern regarding geographical locations (East, South, and West Africa). Although 46 factors influencing DTMV adoption were initially identified, only technology attributes (drought tolerance, yield, pest and disease resistance as a varietal trait), information access (access to climate information services and seed sources), and institutional support (membership of farmers’ group) emerged as the main drivers of DTMV adoption. Conversely, individual characteristics, such as age, gender, marital status, and education, commonly used in adoption studies, did not influence DTMV adoption. These findings highlight the need for a shift in analytical frameworks to prioritize factors directly related to technology attributes, information access, and institutional support. The paper contributes to theoretical frameworks in climate-resilient technology adoption, offering insights for agricultural policy and management in sub-Saharan Africa.